Evaluation of Website Based Information System To Monitor Student Learning Progress In Schools Using ISO/IEC 9126 Standards And GTMetrix - Mahadika, Dhaniaffa Adhimastama; Aristyagama, Yusfia Hafid; Budiyanto, Cucuk Wawan (IJIE (Indonesian Journal of Informatics Education), 2023)
This study aims to evaluate website based information systems that have been developed previously using ISO/IEC 9126 Standards and GTMetrix. Testing of website based information systems using ISO/IEC 9126 is carried out by  information system expert,  users, and testing using GTMetrix, the user referred to in the test these are administrators, teachers, and student parents. Testing of information system experts takes four measures of quality including functionality, reliability, usability, and portability, while testing on users takes three measures including functionality, usability, and portability, and testing using GTMetrix takes a measure of quality efficiency and serves to assess the performance of the website-based information system developed. The results obtained from the  evaluation were testing of  information system expert getting a score of 91.17%, administrator user getting a score of 95.11%, teacher user getting a score of 91.35%, student parents getting a score of 83.4%, and testing using  GTMetrix getting a score of 86.13% or Grade B. Based on the results of the evaluation using ISO/IEC 9126, it was found that the testing using  ISO/IEC 9126 for the tested website-based information system has been meet the expectations of users, especially parents and the school.